Book Review - Barbieri, Umberto (OverHolland, 2005)
Wim Denslagen Romantisch modernisme: Nostalgie in de monumentenzorg Amsterdam (SUN) 2004, 255 pp. Andrés Duany, Elizabeth Plater-Zyberk, Robert Alminana (red.) The new civic art: Elements of Town Planning New York (Rizzoli) 2003, 416 pp.